Pharmacokinetic characterization of favipiravir in patients with COVID-19 - Gulhan, Rezzan; Eryuksel, Emel; Oglu, Medine Gulcebi Idriz; Culpan, Yekta; Toplu, Aylin; Kocakaya, Derya; Tigen, Elif; Sengel, Buket Erturk; Sili, Uluhan; Yildizeli, Sehnaz Olgun; Balcan, Mehmet Baran; Elci, Abdullah; et al. (WILEY, 2022)
This prospective observational study describes the pharmacokinetic characteristics of favipiravir in adult patients hospitalized for mild to moderate COVID-19 with a positive RT-PCR test. Favipiravir was administered for 5 days, with a loading dose of 3200 mg and a maintenance dose of 1200 mg/day. Serial blood samples were collected on Day 2 and Day 4 of the therapy. Laboratory findings of the patients (n = 21) and in-hospital mortality were recorded. Favipiravir concentrations exhibited substantial variability and a significant decrease during the treatment of COVID-19. The median favipiravir trough concentration (C0-trough) on Day 2 was 21.26 (interquartile range {[}IQR], 8.37-30.78) mu g/mL, whereas it decreased significantly to 1.61 (IQR, 0.00-6.41) mu g/mL on Day 4, the area under the concentration-time curve decreased by 68.5\%. Day 2 C0-trough of female patients was higher than male patients. Our findings indicate that favipiravir concentrations show significant variability during the treatment of COVID-19 and therapeutic drug monitoring may be necessary to maintain targeted concentrations.
Keywords: COVID; favipiravir; pharmacokinetics; therapeutic drug monitoring